Alternative energy in power electronics - Rashid, Muhammad H. (Muhammad Harunur), 1945- (Butterworth-Heinemann, 2015)
"In today's industrialized world, energy became vital to all human activities including manufacturing, data processing, heating, cooling, lighting, transportation, food processing, etc., yet it is invisible for most of us. Today's energy generation technologies are undergoing a paradigm shift; the solution to our current dilemma requires more renewable contribution as well as the more efficient utilization of conventional energy sources. Recognizing this importance, this chapter focuses on energy sources and energy generation technologies including, coal, hydroelectric, nuclear, solar, wind, ocean, and several others. Alternative energy technologies received great interest in recent years due to environmental impact, greenhouse gas emissions, national energy security, and increasing cost of fossil fuel based sources. With particular emphasis on renewable and alternative energy systems, characteristic features of the renewable energy sources have been reviewed. Since power electronics is a key enabling technology for renewable energy utilization, power electronic converters and interfaces that are used for grid interconnection and stand-alone operation have been presented"--